Monocyte count as a prognostic biomarker in patients with idiopathic pulmonary fibrosis - Kreuter, Michael; Lee, Joyce S.; Tzouvelekis, Argyrios; Oldham, Justin M.; Molyneaux, Philip L.; Weycker, Derek; Atwood, Mark; Kirchgaessler, Klaus-Uwe; Maher, Toby M. (American journal of respiratory and critical care medicine, 2021)
Rationale: There is an urgent need for simple, cost-effective prognostic biomarkers for idiopathic pulmonary fibrosis (IPF); biomarkers that show potential include monocyte count. Objectives: We used pooled data from pirfenidone and IFN gamma-1b trials to explore the association between monocyte count and prognosis in patients with IPF. Methods: This retrospective pooled analysis included patients (active and placebo arms) from the following four phase III, randomized, placebo-controlled trials: ASCEND (NCT01366209), CAPACITY (NCT00287729 and NCT00287716), and INSPIRE (NCT00075998). Outcomes included IPF progression (>= 10% absolute decline in FVC% predicted,>= 50mdecline in 6-minute-walk distance, or death), all-cause hospitalization, and all-cause mortality over 1 year. The relationship between monocyte count (defined as time-dependent) and outcomes was assessed using bivariate and multivariable models. Measurements and Main Results: This analysis included 2,067 patients stratified by monocyte count (at baseline:,0.603109 cells/L [n = 1,609], 0.60 to <0.95x10(9) cells/L [n= 408], and >= 0.95x10(9) cells/L [n = 50]). In adjusted analyses, a higher proportion of patients with monocyte counts of 0.60 to,0.953109 cells/L or >0.953109 cells/L versus,0.603109 cells/L experienced IPF progression (P= 0.016 and P = 0.002, respectively), all-cause hospitalization (P= 0.030 and P = 0.003, respectively), and all-cause mortality (P= 0.005 and P, 0.001, respectively) over 1 year. Change inmonocyte count frombaseline was not associated with any of the outcomes over 1 year and did not appear to be affected by study treatment. Conclusions: In patients with IPF, elevated monocyte count was associated with increased risks of IPF progression, hospitalization, and mortality. Monocyte count may provide a simple and inexpensive prognostic biomarker in IPF.
Gesehen am 16.09.2021